Role of Habit and Value Perceptions on m-Learning Outcomes. Issue 6 (1st November 2020) - Yoo, Dong Kyoon; Cho, Sunyoung
ABSTRACT: The significance of mobile devices in digital learning is growing fast as they allow users to have easier access to content materials and build engaging interactions with others. On the other hand, there exist concerns without enough systematic investigations that users may be distracted when using mobile devices for learning. Drawing upon the value-based adoption perspective in combination with habit, this study investigates m-learning dynamics using a survey method with 257 participants. The results showed that habit has a direct impact on utilitarian/hedonic values and m-learning continuance intention, but a distal influence on learning outcomes. The analysis of results by the mobile device types indicates differences in m-learning dynamics between users with handheld mobile devices and those with laptops. For handheld mobile device users, hedonic value has a greater impact on learning outcomes than utilitarian value does, while utilitarian value has more influence on learning outcomes for laptop users.